Tính chất cơ học của vật liệu polyme compozit từ nhựa epoxy DER-331 gia cường bằng mat lai tạo dứa dại/thủy tinh - Diệu, Trần Vĩnh; Minh Ngọc, Phan Thị; Thành, Nguyễn Đắc; Duy Linh, Nguyễn Phạm; Tiến, Bùi Văn (Vietnam Journal of Chemistry, 2014)
Sisal fiber is an effective reinforcement for epoxy resin. Mechanical properties of a sisal fiber mat reinforced epoxy resin composite are higher in comparison with those of epoxy resin, especially in impact strength, which is 369% higher. The effect of alkali treatment of sisal fiber on the interfacial shear strength (IFSS) and mechanical properties of sisal fiber mat reinforced epoxy DER-331 resin composites were studied. It has shown that average IFSS is 94% higher, tensile strength and flexural strength of composite are 72% and 31% higher respectively in comparison with those of untreated fibers. In order to improve mechanical properties of composite material, sisal fiber mat was replaced partly by glass fiber mat. Owing to the superior properties of glass fibers, the mechanical properties of the hybrid composites increase with the increasing of weight fraction of glass fibers. The observation has shown that optimum glass fiber mat loadings for the hybrid composite was 50 wt.%. Water absorption of the hybrid composite was reduced from 8.5 to 2.4% in comparison with non-hybridized sisal fiber mat reinforced epoxy resin composite. Scanning electron microscopic studies were carried out to study the fiber-matrix adhesion.